Factors promoting and limiting antimicrobial resistance in the environment – Existing knowledge gaps - Goryluk-Salmonowicz, Agata; Popowska, Magdalena (Frontiers in Microbiology, 2022)
The dissemination of multidrug-resistant bacteria strains and genes carrying antibiotic resistance is currently considered to be one of the most important global problems. The WHO emphasizes the need to contain the spread of Antimicrobial Resistance (AMR) from all possible sources. There have been many international initiatives grouping scientists studying this phenomenon, and quite a lot of scientific projects devoted to this problem have already been carried out. So far, several strategies have been developed that can inhibit the AMR spread. In this mini-review, we highlight overlooked aspects of the problem that seem to be crucial for creating a comprehensive picture of AMR, especially in the context of the One Health approach.